Towards Achieving A 'Second Green Revolution'-The Role of Radiation Technology in Food Processing Management - Sitalakshmi, S. (Indian Journal of Marketing, 2009)
Technology is the mainstay of modern industry and trade. The pace of globalization of trade and commerce in today's world is determined by emerging technologies in every area of business. Of these, the eco-friendly technologies are gaining ground as environmental pollution stands as the biggest threat to the survival of mankind. Radiation technology is an emerging technology that comes under the banner 'radiation for peaceful purposes'. It has a wide range of applications in the areas of Health & Hygiene, Medicine, Pharmaceuticals, Agriculture etc. This paper discusses the application of radiation technology to the processing of food so as to improve post-harvest storage facilities & hygiene and pave way for processed-food.